Building climate services capacity in Rwanda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
The Rwanda Climate Services for Agriculture project is a four-year initiative (2016-2019) that seeks to transform Rwanda’s rural farming communities and national economy through improved climate risk management. The project’s goal is to improve agricultural planning and food security management in the face of a variable and changing climate at both local and government levels. In order to do so, project staff will work directly with technical officers, policy and decision makers within the Government of Rwanda, as well as with farmers and other key stakeholders in the country’s agriculture sector.